Internal Sulphate Reaction (ISR) as degradation of the cement matrix: behavior of pastes dosed with different amounts of contamination by sulfate - Brandão Capraro, Ana Paula; Farias de Medeiros, Marcelo Henrique; Hoppe Filho, Juarez; Portella Bragança, Mariana; Portella, Kleber Franke; Oliveira, Isabela Cristina (Revista ALCONPAT, 2017)
The present work, developed in the scope of the R&D Program of ANEEL, project 6491-0301/2013, aims to evaluate how different levels of sulfide contamination interfere with the microstructural and mechanical characteristics of the cement pastes when they are submitted to two exposure conditions: wetting and drying cycle and aerated tank. For an analysis of the deteriorating mechanism, four series of cement pastes, one reference and three contaminated by sulfur, were evaluated by non-fresh tests (consistency and specific mass) and resistance (axial compression and flexural tensile strength, dimensional variation and XRD). At the end of the study period (84 days) it was noted that the auxiliary assays did understand the mechanism but that it would still be at an early stage.